Determination of water quality for irrigation at the entrance of Radoniqi accumulation with physicochemical and bacteriological parameters for the period of spring 2021 - Bajraktari, Naser; Elshani, Arsim; Berisha, Defrime (Emirates Journal of Food and Agriculture, 2022)
Water quality research for irrigation at the inlet of Radoniqi reservoir with physicochemical, heavy metals and bacteriological parameters was conducted in the spring quarter period 2021, focusing on two sampling points: at the entrance of the derivation canal (Lumbardhi River of Deçan) and at the exit of derivative canal (near the Lake) as the main supply point. In order to know the degree of its quality, the identification of polluting sources has been performed, which in turn will enable the necessary steps to be taken by the management of RWC ‘Gjakova’ for their isolation. Also, to complete the study, research was done on heavy metals and other nutrients, in all sampling sites, and especially where there are significant sources of surface water pollution, as a result of human activity and discharge of untreated urban waters. So, the focus or purpose of the research is to reflect the situation as realistically as possible and this was done by determining the bacteria by the membrane filter method by counting the colonies in Petri dishes with VRB-agar, M-Endo Agar Less, CCA.